Tricky Vic : the impossibly true story of the man who sold the Eiffel Tower - Pizzoli, Greg (Viking, an imprint of Penguin Group, 2015)
In the early 1900s, Robert Miller, a.k.a. "Count Victor Lustig," moved to Paris hoping to be an artist. A "con" artist, that is. He used his ingenious scams on unsuspecting marks all over the world, from the Czech Republic, to Atlantic ocean liners, and across America. Tricky Vic pulled off his most daring con in 1925, when he managed to "sell" the Eiffel Tower to one of the city's most successful scrap metal dealers! Six weeks later, he tried to sell the Eiffel Tower all over again. Vic was never caught. For that particular scam, anyway.